Zasadnicze przejawy ingerencji w prawa podmiotowe prywatne jednostek przez III Rzeszę - Kruszewski, Tomasz; Górnicki, Leonard (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article analyzes the most important manifestations of limitation of subjective rights of private individuals by the Third Reich. The authors begin the article by undermining by the national socialist regime one of the fundamental principles, which is equality before the law. Then, the authors analyze the violations of particulars individual rights of private individuals.The purpose of the authors is to demonstrate that the self-reliance of aperson Eigenständigkeit has ceased to be an essential element of private law in the national socialist legal order. The sphere in which the subject of law could freely regulate the legal situation created by acts of his will, became clearly restricted. But also, and even more specifically, the sphere of traditionally protected civil rights of private individuals has fallen. The interference of the national socialist regime in the sphere of human privacy followed by changes both in civil and in public law. The existence of a formal legal basis was supposed to exclude the unlawfulness of the behavior of the subjects of the law, especially the state, its organs and institutions, but in the light of the idea ofthe law of the civilized nations it was “statutory lawlessness”.
Keywords: prawa podmiotowe osób prywatnych; prawa do prywatności Persönlichkeitsrechtes; nierówność wobec prawa; rasizm; prawo rasowe Rassenrecht; prawo norymberskie; eugenika; eutanazja